The epidemiology of rabies and canine distemper in the Serengeti, Tanzania. - Cleaveland, S. (University of London, 1996)
Rabies and canine distemper are fatal diseases of mammals and of concern in the Serengeti, Tanzania both for public health and wildlife conservation. This study investigates the epidemiology of these diseases through cross-sectional and longitudinal studies of two domestic dog populations bordering the Serengeti National Park. Chapter 2 demonstrates differences in demographic and behavioural characteristics between the two populations, leading to predictions of distinct patterns of rabies and canine distemper infection, and the requirement for different strategies of disease control. Chapter 3 compares the use of three rabies serological tests for seroepidemiological studies of domestic dogs. Non-specificity precluded use of the indirect ELISA, but a liquid-phase blocking ELISA (BE) and neutralization test (RFFIT) demonstrated rabies seropositivity among unvaccinated Serengeti dogs. The poor agreement between BE and RFFIT in unvaccinated dogs led to an investigation of specificity, which indicated that the BE was the more specific assay. In Chapter 4, incidence data and virus typing suggested that dogs, not wildlife, are the reservoir of rabies in the Serengeti. Case surveillance data indicated that rabies persists in higher- density dog populations, but occurs only sporadically in lower-density dog and wild carnivore populations. Rabies seropositivity occurred in dogs remaining healthy, demonstrating the existence of atypical infections. Mathematical models showed that rabies persistence in Serengeti dogs was more likely if seropositives were infectious carriers, rather than slow-incubators or immune animals. In Chapter 5, analysis of case-morbidity, mortality and age-seroprevalence data indicated that canine distemper was stably endemic in higher-density dog populations, but sporadically epidemic in lower-density dog populations. In conclusion, higher-density dog populations to the west of the Serengeti National Park are the most likely reservoir of both rabies and canine distemper in the Serengeti and disease control strategies should therefore focus on controlling infection in these populations.